TINGKAT PEMANFAATAN SUMBER DAYA IKAN HASIL TANGKAPAN DI PERAIRAN JEMBER - Ariesia A. Gemaputri (Universitas Gadjah Mada, 2013)
The purpose of this research was to determine the Maximum Sustainable Yield and Catch Per Unit of Effort as a management tools to solve the ﬁ sh capture in the waters of Puger sub-district, Jember district. This research was conducted by direct observation method in the ﬁ eld, and collected the statistical data from the Animal, Fisheries and Marine Department of Jember, and also from Fishing port of Puger. The statistical data as seconday data was obtained in time series from 2005 to 2011 (7 year), namely ﬁ sh production and catching effort, then it was analyze dusing the Schaefer method to ﬁ nd thevalue of MSY and CPUE. The MSY was analyzed using regression formula Y = a – bX (Y= CPUE, X= effort). The results showed the CPUEin the year 2007 was the highest approximately 23.47kg/trip. The Lowest CPUE was occurred in the year 2005 approximately12.38kg/trip. Based onthe regression of Y= 33.213 -0.00004X, the MSY was found at 6,894,396.1kg/year,while the maximum catch effort was 207,581.25 trips/year